Weight and Veterans' Environments Study (WAVES) I and II: Rationale, Methods, and Cohort Characteristics. Issue 3 (March 2018) - Zenk, Shannon N.; Tarlov, Elizabeth; Powell, Lisa M.; Wing, Coady; Matthews, Stephen A.; Slater, Sandy; Gordon, Howard S.; Berbaum, Michael; Fitzgibbon, Marian L.
Purpose: To present the rationale, methods, and cohort characteristics for 2 complementary "big data" studies of residential environment contributions to body weight, metabolic risk, and weight management program participation and effectiveness. Design: Retrospective cohort. Setting: Continental United States. Participants: A total of 3 261 115 veterans who received Department of Veterans Affairs (VA) health care in 2009 to 2014, including 169 910 weight management program participants and a propensity score–derived comparison group. Intervention: The VA MOVE! weight management program, an evidence-based lifestyle intervention. Measures: Body mass index, metabolic risk measures, and MOVE! participation; residential environmental attributes (eg, food outlet availability and walkability); and MOVE! program characteristics. Analysis: Descriptive statistics presented on cohort characteristics and environments where they live. Results: Forty-four percent of men and 42.8% of women were obese, whereas 4.9% of men and 9.9% of women engaged in MOVE!. About half of the cohort had at least 1 supermarket within 1 mile of their home, whereas they averaged close to 4 convenience stores (3.6 for men, 3.9 for women) and 8 fast-food restaurants (7.9 for men, 8.2 for women). Forty-one percent of men and 38.6% of women did not have a park, and 35.5% of men and 31.3% of women did not have a commercial fitness facility within 1 mile. Conclusion: Drawing on a large nationwide cohort residing in diverse environments, these studies are poised to significantly inform policy and weight management program design.